?STUDIES ON THE EQUILIBRIUM RELATIVE HUMIDITY AND MOISTURE SORPTION ISOTHERM OF MANGO, GUAVA AND MULBERRY FRUIT POWDERS - KHAN, F.M; JABBAR, ABDUL; UDDIN, EUAZ (Biological Sciences - PJSIR, 1996)
Reasonably good quality fruit powders from mango, guava and mulberry fruits prepared by hot air drying technique were subjected to ERH investigations. The initial moisture content of these dehydrated products were 2.0, 1.8 and 4.0 %, respectively. The euqilibrium moisture content for quality retention were estimated as 1.54, 1.62 and 3.80% respectively and the corresponding optimum euqilibrium relative humidities for these products were in the rang eof 51.4-71.4,40.0-51.4 and 22.0-40.0 respectively. The standard humidity conditions, to which the products were exposed, ranged from 11.0 to 92.0%. Mold-growth appeared after 28,21 and 15 days respectively in mango, guava and mulberry when placed under 92% humidity, whereas under 79.2% ERH, the first mold growth in these products was observed after 40,32 and 25 days respec- tively. These studies indicated that the optimum ERH for maintianing good conditions of flow-ability, colour and other physical characteristics was around 51.4% for mango and guava but mulberry powder required more depressed condition of ERH values i.e. 22.0% for maintaining good quality characteristics during the storage.